2021
DOI: 10.1111/gcb.15650
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance type and species life history predict mammal responses to humans

Abstract: Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 88 publications
9
88
0
Order By: Relevance
“…Wildlife assemblages across the world are often affected by human development and activity (Crooks et al, 2010;Suraci et al, 2021) and gross primary productivity (Willig et al, 2003), but none of these factors affected the ψ or p of grey fox site use in our analyses using sites from across the contiguous United States. Many studies have reported that anthropogenic development has a negative effect on grey foxes (Kowalski et al, 2015;Lombardi et al, 2017;Nickel et al, 2020;Ordeñana et al, 2010), yet other studies found that they use a range of human development intensities (Harrison, 1997;Kapfer & Kirk, 2012;Riley, 2006;Suraci et al, 2021) and that human activity has a positive effect on grey foxes (Nickel et al, 2020;Rota et al, 2016). These varying effects of anthropogenic development may be due to more complex factors, such as grey foxes using anthropogenic landscapes to avoid coyotes (Lesmeister et al, 2015;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Wildlife assemblages across the world are often affected by human development and activity (Crooks et al, 2010;Suraci et al, 2021) and gross primary productivity (Willig et al, 2003), but none of these factors affected the ψ or p of grey fox site use in our analyses using sites from across the contiguous United States. Many studies have reported that anthropogenic development has a negative effect on grey foxes (Kowalski et al, 2015;Lombardi et al, 2017;Nickel et al, 2020;Ordeñana et al, 2010), yet other studies found that they use a range of human development intensities (Harrison, 1997;Kapfer & Kirk, 2012;Riley, 2006;Suraci et al, 2021) and that human activity has a positive effect on grey foxes (Nickel et al, 2020;Rota et al, 2016). These varying effects of anthropogenic development may be due to more complex factors, such as grey foxes using anthropogenic landscapes to avoid coyotes (Lesmeister et al, 2015;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…Following the recommendations of MacKenzie et al (2017), instead of estimating the proportion of total study area occupied by each species and the detection probability of a species, respectively, we defined the parameters of interest (occupancy and detection probability) as the probability of site use (ψ) and the intensity of site use ( p ; i.e. the probability a species returns to a site, given use), respectively, to control for the potential bias that can come from closely spaced cameras that potentially violate spatial independence (Kery & Royle, 2008; MacKenzie et al, 2002, 2017; Suraci et al, 2021). Multiple covariates were correlated with other predictors (Pearson's r > 0.7).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations